Raman spectroscopy provides a non-invasive approach for determining biochemical composition of the pregnant cervix in vivo - O'Brien, Christine M. (2014)
The molecular changes that occur with cervical remodelling during pregnancy are not completely understood. This paper reviews Raman spectroscopy, an optical technique for detecting changes in the pregnant cervix, and reports preliminary studies on cervical remodelling in mice that suggest that the technique provides advantages over other methods. Conclusion: Raman spectroscopy is sensitive to biochemical changes in the pregnant cervix and has high potential as a tool for detecting premature cervical remodelling in pregnant women.